Dementia in China: epidemiology, clinical management, and research advances. Issue 1 (January 2020) - Jia, Longfei; Quan, Meina; Fu, Yue; Zhao, Tan; Li, Yan; Wei, Cuibai; Tang, Yi; Qin, Qi; Wang, Fen; Qiao, Yuchen; Shi, Shengliang; Wang, Yan-Jiang; et al.
Summary: China has the largest population of patients with dementia in the world, imposing a heavy burden on the public and health care systems. More than 100 epidemiological studies on dementia have been done in China, but the estimates of the prevalence and incidence remain inconsistent because of the use of different sampling methods. Despite improved access to health services, inadequate diagnosis and management for dementia is still common, particularly in rural areas. The Chinese Government issued a new policy to increase care facilities for citizens older than 65 years, but most patients with dementia still receive care at home. Western medicines for dementia symptoms are widely used in China, but many patients choose Chinese medicines even though they have little evidence supporting efficacy. The number of clinical trials of Chinese and western medicines has substantially increased as a result of progress in research on new antidementia drugs but international multicentre studies are few in number. Efforts are needed to establish a national system of dementia care enhance training in dementia for health professionals, and develop global collaborations to prevent and cure this disease.